Innovation in Public Services of the Surakarta City Government During the Leadership of Gibran Rakabuming Raka - Rifi Rivani Radiansyah; Isnandi Abdul Rozak Riaji; Mochamad Fattahidayah Dinata (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Transformation in public services is a form of the Surakarta city government's efforts to solve the problems that exist in the people of Surakarta which include (1) Increasing poverty rates, (2) Low increase in HDI and (3) the expected value has not been achieved in SMEs in complaint, suggestion and input services from 2019 to 2020. The purpose of the research is to find out how public service innovation in the Surakarta City Government during the leadership of Gibran Rakabuming Raka through the Solo Techno Park and ULAS programs. The methods used in this study are descriptive Qualitative Research Methods, observational data collection techniques, FGD and documentation with the research object, namely the Surakarta City Government.Based on the results of the research, various findings have been found in the processing of public service innovations in the city of Surakarta during the leadership of Gibran Rakabuming Raka. As the focus of the research which better describes public service innovations in the city of Surakarta. There are 6 innovation indicators stated in the General Guidelines for State Administration Services, including Novelty, Usefulness, Providing Solutions, Sustainability, Replicability and Compatibility. At the end of the study, it can be concluded that Public Service Innovation in the City of Surakarta during the leadership of Gibran Rakabuming Raka has implemented innovations in good public services even though there are still things that need to be improved and improved